Identifikasi Drug-Related Problems (DRPs) pada Pasien Gagal Ginjal Kronik di Instalasi Rawat Inap RSUP Dr. Sitanala Tangerang Tahun 2019-2021 - Megawati, Sefi; Sopiahani, Syifa; Fathonah, Nuriyatul (Jurnal Ilmiah Medicamento, 2024)
Chronic kidney disease (CKD) is characterized by the gradual decline of kidney function over one year or more. The primary functions of the kidneys include maintaining fluid balance, regulating blood electrolyte levels, ensuring acid-base homeostasis, and removing waste products and excess electrolytes. Drug-related problems (DRPs) are medication-related issues that can negatively impact patients' quality of life. This study aims to determine the prevalence of DRPs in CKD patients treated at Dr. Sitanala Hospital, Tangerang, during 2019-2021. This descriptive study used retrospective data collection, presenting the results as percentages. Ninety-two (92) patients met the inclusion criteria, with a gender distribution of 48 males (52.17%) and 44 females (47.83%). The most common age group was 56-65, accounting for 28 cases (30.43%). The prevalence of DRPs in hospitalized CKD patients was found to be 89 cases (96.74%), with the following breakdown: 19 cases (16.67%) of unnecessary drug therapy (TOTP), 15 cases (18%) requiring additional therapy (KTT), 79 cases (69.3%) of ineffective drugs (OTE), and 1 case (0.88%) of drugs with too high a dose (DTT), while no cases of drugs with too low a dose (DTR) were identified.